2011
DOI: 10.1126/science.1209200
|View full text |Cite
|
Sign up to set email alerts
|

Endocannabinoid Hydrolysis Generates Brain Prostaglandins That Promote Neuroinflammation

Abstract: Phospholipase A2 (PLA2) enzymes are considered the primary source of arachidonic acid for cyclooxygenase (COX)-mediated biosynthesis of prostaglandins. Here, we show that a distinct pathway exists in brain, where monoacylglycerol lipase (MAGL) hydrolyzes the endocannabinoid 2-arachidonoylglycerol to generate a major arachidonate precursor pool for neuroinflammatory prostaglandins. MAGL-disrupted animals show neuroprotection in a parkinsonian mouse model. These animals are spared the hemorrhaging caused by COX … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

30
679
4
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 619 publications
(715 citation statements)
references
References 39 publications
30
679
4
2
Order By: Relevance
“…Recent studies show that the anti-inflammatory and neuroprotective effects by inhibition of MAGL are not mediated by CB1 or by CB2 receptors. 19,21,27 In addition, inhibition of CB1 receptors only partly blocks 2-AG-produced neuroprotective effects in TBI. 22 This suggests that there may be other mechanisms mediating the anti-neuroinflammatory and neuroprotective effects produced by inhibition of 2-AG metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies show that the anti-inflammatory and neuroprotective effects by inhibition of MAGL are not mediated by CB1 or by CB2 receptors. 19,21,27 In addition, inhibition of CB1 receptors only partly blocks 2-AG-produced neuroprotective effects in TBI. 22 This suggests that there may be other mechanisms mediating the anti-neuroinflammatory and neuroprotective effects produced by inhibition of 2-AG metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…The moderate dose employed here should also be devoid of the decreased CB1 receptor function observed at high doses of the drug (Schlosburg et al, 2010;Kinsey et al, 2013), although, differently from these previous reports, in our case the duration of the treatment was longer. As JZL184-induced increase in 2-AG levels is dependent on the dose as well as the duration of the treatment (Kinsey et al, 2013), one possibility is that in healthy mice (controls) chronic administration of JZL184 may have exacerbated the 2-AG-signaling, along with an eventual loss of MAGL activity-dependent neuroprotective mechanisms (Nomura et al, 2011), to an extent sufficient to produce the behavioral responses observed, and which usually occur at high doses of CB1 receptor agonists (Rey et al, 2012). Indeed, JZL184 and combo treatments induced a statistically significant higher increase in 2-AG level in controls as compared with CUS animals ( Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the levels of 2-AG and AA were shown to inversely correlate with the free AA generated upon hydrolysis of 2-AG which was shown to act as precursor for eicosanoid biosynthesis [4]. Prostanoids are a family of lipid mediators that play key roles in both inflammatory and neuropsychiatric processes.…”
Section: Introductionmentioning
confidence: 99%